Interconnection mechanism and strengthening behavior of nano-silver sintered joints for silicon carbide power module packaging: A combined EBSD and nanoindentation study - Chao Gu; Xiao Hu; Xuyang Yan; Wei Chen; Junwei Chen; Kai Lu; Tao Wang; Guoqi Zhang; Jiajie Fan (Journal of Materials Research and Technology, 2025)
Investigating the interconnection and strengthening mechanisms of die-attach layers is instrumental for advancing die attach process toward low-pressure and, ultimately, pressureless sintering while maintaining reliability. This study compares the microstructure and micromechanical heterogeneity of the pressure-assisted and pressureless regions in SiC die attach to elucidate the interconnection and strengthening mechanisms. Recrystallized grains make up 71.7 % of the pressureless region, markedly lower than the approximately 90 % observed in the pressure-assisted region, resulting in a higher porosity in the former. Evidence of both continuous dynamic recrystallization and discontinuous dynamic recrystallization is identified throughout the sintered layer. Microhardness reveals that the pressureless zone exhibits a hardness of 0.373 GPa, significantly lower than left (0.745 GPa) and right (1.832 GPa) of pressure-assisted region. All three regions share an average grain size of 400 ± 50 nm, and geometrically necessary dislocation density in pressureless zone exceeds that in pressure-assisted areas, neither of which can account for the difference in micromechanical performance. In contrast, the statistically stored dislocation (SSD) densities on the left and right of the pressure-assisted region are approximately 4.74 × 1014 m−2 and 2.88 × 1015 m−2, respectively—substantially higher than the 2.88 × 1014 m−2 measured in the pressureless region. Collectively, these findings demonstrate that dislocation strengthening, and particularly SSD density, constitutes the dominant strengthening mechanism in silver sintered layers. This work not only provides new insights for enhancing reliability under low-pressure and pressureless sintering but also establishes a theoretical foundation for optimizing sintering material formulations.